Oridonin alleviates the inhibitory effect of lipopolysaccharide on the proliferation and osteogenic potential of periodontal ligament stem cells by inhibiting endoplasmic reticulum stress and NF-κB/NLRP3 inflammasome signaling - Junhao Jiang; Nong Zhang; Haibo Song; Ya Yang; Juan Li; Xiaoli Hu (BMC, 2023)
Abstract Background The aim of this study was to investigate the protective effect and mechanism of oridonin in an in vitro lipopolysaccharide (LPS)-induced human periodontal ligament stem cells (hPDLSCs) model of periodontitis. Methods Primary hPDLSCs were isolated and cultured, and then the expression of surface antigens CD146, STRO-1 and CD45 of hPDLSCs was detected by flow cytometry. The mRNA expression level of Runx2, OPN, Col-1, GRP78, CHOP, ATF4 and ATF6 in the cells was tested by qRT-PCR. MTT was taken to determine the cytotoxicity of oridonin at different concentrations (0-4 μM) on hPDLSCs. Besides, ALP staining, alizarin red staining and Oil Red O staining were utilized to assess the osteogenic differentiation (ALP concentration, mineralized calcium nodule formation) and adipogenic differentiation abilities of the cells. The proinflammatory factors level in the cells was measured by ELISA. The protein expression level of NF-κB/NLRP3 pathway-related proteins and endoplasmic reticulum (ER) stress-related markers in the cells were detected by Western blot. Results hPDLSCs with positive CD146 and STRO-1 expression and negative CD45 expression were successfully isolated in this study. 0.1-2 μM of oridonin had no significant cytotoxicity on the growth of hPDLSCs, while 2 μM of oridonin could not only greatly reduce the inhibitory effect of LPS on the proliferation and osteogenic differentiation of hPDLSCs cells, but also inhibit LPS-induced inflammation and ER stress in hPDLSCs cells. Moreover, further mechanism research showed that 2 μM of oridonin suppressed NF-κB/NLRP3 signaling pathway activity in LPS-induced hPDLSCs cells. Conclusions Oridonin promotes proliferation and osteogenic differentiation of LPS-induced hPDLSCs in an inflammatory environment, possibly by inhibiting ER stress and NF-κB/NLRP3 pathway. Oridonin may have a potential role in the repair and regeneration of hPDLSCs.